Complexity of sliding Shilnikov connections in Filippov systems & Hyperbolicity for infinite delayed difference equations - Cunha, Matheus Gonçalves Cassiano da, 1993- (2024)
Orientador: Douglas Duarte Novaes, Gabriel Ponce